Diversity and temporal variation of the bird community in paddy fields of Kadhiramangalam, Tamil Nadu, India - Chaithra Shree Jayasimhan; Pramod Padmanabhan (Journal of Threatened Taxa, 2019)
Paddy, a major food crop of India, provides a variety of habitats in a short period of time and supports diverse organisms. Paddy fields also harbour many birds with varying species composition across the different cultivation phases of paddy. This study, conducted in the paddy fields of Kadhiramangalam, Tamil Nadu, India, recorded the bird community composition there during the various cultivation phases of paddy. The bird community data was analysed and a total of 87 bird species were recorded from the study area belonging to 41 families and 13 orders. The growth phase (PS 3) is the most diverse phase. The bird composition showed a significant variation across the paddy cultivation phases with overall average dissimilarity of 71.41%. The patterns shown by graphs of bird species composition across the paddy cultivation phases is based on guild, habitat usage and order overlap and elucidates that the change in bird community composition temporally can be attributed to the niche variability across the paddy cultivation phases. The major species contributing to these changes observed are Black-headed Munia, Baya Weaver, Common Sandpiper, Barn Swallow, Common Myna, and Black Drongo in this region.